Intracellular forces during guided cell growth on micropatterns using FRET measurement. Issue 4 (26th February 2015) - Suffoletto, Kevin; Ye, Nannan; Meng, Fanjie; Verma, Deepika; Hua, Susan Z.
Abstract: Interaction of cells with extracellular matrix (ECM) regulates cell shape, differentiation and polarity. This effect has been widely observed in cells grown on substrates with various patterned features, stiffness and surface chemistry. It has been postulated that mechanical confinement of cells by the substrate causes a redistribution of tension in cytoskeletal proteins resulting in cytoskeletal reorganization through force sensitive pathways. However, the mechanisms for force transduction during reorganization remain unclear. In this study, using FRET based force sensors we have measured tension in an actin cross-linking protein, α-actinin, and followed reorganization of actin cytoskeleton in real time in HEK cells grown on patterned substrates. We show that the patterned substrates cause a redistribution of tension in α-actinin that coincides with cytoskeleton reorganization. Higher tension was observed in portions of cells where they form bridges across inhibited regions of the patterned substrates; the attachment to the substrate is found to release tension. Real time measurements of α-actinin tension and F-actin arrangement show that an increase in tension coincides with formation of F-actin bundles at the cell periphery during cell-spreading across inhibited regions, suggesting that mechanical forces stimulate cytoskeleton enhancement. Rho-ROCK inhibitor (Y27632) causes reduction in actinin tension followed by retraction of bridged regions. Our results demonstrate that changes in cell shape and expansion over patterned surfaces is a force sensitive process that requires actomyosin contractile force involving Rho-ROCK pathway.